Ionic liquid embedded in polymeric membrane for high pressure CO2 separation - Mohshim, D.F. (Italian Association of Chemical Engineering - AIDIC, 2015)
In recent years, the societies are looking forward for green energy consumption thus making natural gas usage increased tremendously from the last few decades. The increasing natural gas demand has led to increasing number of environmental friendly research in natural gas purification techniques. Membrane separation technology is one of the green methods that experience breakthrough, substantial growth and advances for the carbon dioxide separation from natural gas. The advantages of membrane separation technology covered the simplicity in process, low energy consumption, low carbon and water footprint as well as more environmental compatibility. In particular, the current commercialized membranes are polymeric types such as polyimides as well as cellulose acetate. However, the applications of the commercialized membranes are still limited to remove low CO2 content in the gas stream. Hence, the membrane improvement idea came across to develop membranes that can be applied for high CO2 content separation. This paper intended to present our advanced polymeric membrane fabricated with the addition of ionic liquid. The separation performance was tested at various pressure ranging from 10 to 30 bar and the ideal separation reached up to 70. The fabricated membrane was also having dense morphology as analysed by FESEM which is preferable for gas separation. These results are believed to be an extended and novel future direction for membrane gas separation. Copyright Â© 2015, AIDIC Servizi S.r.l.,.